2013
DOI: 10.1017/s0022149x12000855
|View full text |Cite
|
Sign up to set email alerts
|

The association between multiple intestinal helminth infections and blood group, anaemia and nutritional status in human populations from Dore Bafeno, southern Ethiopia

Abstract: In this cross-sectional study, the associations between helminth infections and ABO blood group, anaemia and undernutrition were investigated in 480 febrile outpatients who visited Dore Bafeno Health Centre, southern Ethiopia, in December 2010. Stool specimens were processed using the Kato-Katz method and examined for intestinal helminth infections. Haemoglobin level was measured using a HemoCue machine and blood group was determined using an antisera haemagglutination test. Nutritional status of the study par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…The observed association between intestinal parasite infection and anemia was expected, as intestinal parasites are risk factors for anemia (64-66). Reduced food intake because of inflammatory reactions induced by lesions in the intestinal mucosa and impaired iron absorption due to worm infections could partly explain this association (58, 67).…”
Section: Discussionmentioning
confidence: 81%
“…The observed association between intestinal parasite infection and anemia was expected, as intestinal parasites are risk factors for anemia (64-66). Reduced food intake because of inflammatory reactions induced by lesions in the intestinal mucosa and impaired iron absorption due to worm infections could partly explain this association (58, 67).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the increased odds of helminth infection among children with blood type A might be due to the possibility that blood type A antigens could contain an increased amount of glycolipid substances that serve as adhesion receptors for hookworm, S. mansoni and A. lumbricoides antigens (Berger et al, 1989). Another study in Ethiopia also documented a significantly lower mean haemoglobin level among patients with blood type AB and slightly lower haemoglobin level in those with blood types A and B than in patients with blood type O (Degarege et al, 2014). Previous studies have also documented high prevalence or intensity of S. mansoni infection in children with blood type A (Ndamba et al, 1997;Degarege et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…This could be due to the nature of the study participants. In addition, variation in socioeconomic and other genetic factors (such as human leucocyte antigen, glyoxalase I system) that may affect an individual's susceptibility for helminth infection may contribute to the unseen difference in the risk of helminth infection between the different blood types in previous studies (Gabr & Mandour, 1991;Cooper et al, 1993;Degarege et al, 2014). As a result, the effect of ABO blood type on helminth infection might have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lower prevalence of malaria in the anemia hotspot areas (eastern Ethiopia), it is less likely that malaria is the cause for the geospatial inequality of anemia in Ethiopia. Furthermore, many studies In Ethiopia revealed that infections such as acute respiratory tract infection, diarrhea and soil-transmitted infection are important contributors in the etiology of anemia (32)(33)(34)(35)(36). However, these infections are not highly concentrated in the eastern part of compared to other parts of Ethiopia (6).…”
Section: Discussionmentioning
confidence: 99%